Multiple Selection Signatures in Farmed Atlantic Salmon Adapted to Different Environments Across Hemispheres - López, María Eugenia; Linderoth, Tyler; Norris, Ashie; Lhorente, Jean Paul; Neira, Roberto; Yáñez, José Manuel (Frontiers in Genetics, 2019)
Domestication of Atlantic salmon started approximately forty years ago, using artificial selection through genetic improvement programs. Selection is likely to have imposed distinctive signatures on the salmon genome, which are often characterized by high genetic differentiation across population and/or reduction in genetic diversity in regions associated to traits under selection. The identification of such selection signatures may give insights into the candidate genomic regions of biological and commercial interest. Here, we used three complementary statistics to detect selection signatures, two haplotype-based (|iHS| and XP-EHH) and one FST -based method (BayeScan) among four populations of Atlantic salmon with a common genetic origin. Several regions were identified for these techniques, that harbored genes such kind1 and chp2 which have been associated with growth-related traits or the kcnb2 gene related to immune system in Atlantic salmon, making them particularly relevant in the context of aquaculture. Our results provide candidate genes to inform the evolutionary and biological mechanisms controlling complex selected traits in Atlantic salmon.